EGb761 protects motoneurons against avulsion-induced oxidative stress in rats - Cheng, Xiao; Liu, Fo-Lin; Zhang, Jun; Wang, Lin-Lin; Li, Fang-lan; Liu, Shu; Zhou, Li-Hua (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background Root avulsion of the brachial plexus causes an oxidative stress reaction in the spinal cord and induces dramatic spinal motoneuron death, while EGb761 is a natural free radical cleaning agent. This study was designed to investigate the protective effects of intraperitoneally injected EGb761 against neural damage following brachial root avulsion.Methods The effect of EGb761 on avulsion-induced motoneuron injury was studied in 26 total groups of (n) rats, treated as follows. Animals in singular number groups received EGb761(50 mg/kg.d) and those in complex number groups received normal saline solution (i.p.), serving as controls. Groups 1-8 were used for the determination of nitric oxide (NO) levels in the serum and injured spinal cord at the 5 d, 2 w, 4 w, and 6 w time points. Groups 9-16 were used for determination of constitutive nitric oxide synthase (cNOS) and inducible nitric oxide synthase (iNOS) levels in injured spinal cord at the 5 d, 2 w, 4 w, and 6 w time points. Groups 17-26 were used for determination of the number of neuronal nitric oxide synthase (nNOS)-positive and surviving motoneurons in injured C7 ventral horn at the 5 d, 2 w, 4 w, 6 w and 8 w time points.Results Compared to control groups, the EGb761 treatment group not only had significant decreased levels of NO in serum at 2 w and 6 w after avulsion, but also had reduced levels of NO specifically in the spinal cord at 2 w, 4 w and 6 w. The cNOS activity in the spinal cord was also significant decreased at 2 w and 4 w, while the iNOS activity in injured C6-T1 spinal segments was reduced at 2 w, 4 w and 6 w. All together, the percentages of NADPH-d positive motoneurons in an injured C7 segment were down-regulated and the number of surviving motoneurons in injured C7 ventral horn was increased at 2 w, 4 w, 6 w and 8 w in treated versus untreated animals.Conclusions Intraperitoneal administration of EGb761 after root avulsion of the brachial plexus exerted protective effects by decreasing the level of NO in spinal cord and serum and the activity of cNOS and iNOS, easing the delayed motoneurons death. EGb761 should be considered in the treatment of brachial plexus nerve injuries.